Virtual Romance: An Analysis of Artificial Intimacy in the Relationship of Players and Characters in the Love and Deepspace Otome Game - Latif Ahmad Fauzan; Meutya Aulia Harza (International Journal of Social, Economic, and Business, 2025)
This study analyzes the artificial intimacy that forms between the players and the love interest character in Love and Deep Space, an innovative 3D visual otome game for young women. In the evolving landscape of online gaming, human-AI interaction has given rise to a new form of digital intimacy. Artificial intimacy, defined as intimacy with AI programmed to be responsive and affective, is built through AI personalization features that enable characters to respond to players deeply, cultivating feelings of being understood, valued, and validated. utilizing the Human-Machine Communication (HMC) framework, which views machines as active communicators, this study is unique due to its focus on Love and Deepspace, a sophisticated and new game and its application of HMC theory to examine the formation of emotional attachment and intimacy, as well as their impact on players real lives.